Complexity and sophistication of Early Middle Paleolithic flint tools revealed through use-wear analysis of tools from Misliya Cave, Mount Carmel, Israel. Issue 154 (May 2021) - Groman-Yaroslavski, Iris; Zaidner, Yossi; Weinstein-Evron, Mina
Abstract: The Early Middle Paleolithic (EMP) is a less-studied phase of the Levantine Middle Paleolithic, attributable to the small number of sites discovered. Drawing on the dense archaeological accumulations at Misliya Cave, Mount Carmel, Israel, the present study seeks to trace EMP daily activities and behavioral patterns through the prism of use-wear analysis. The emergence of the laminar and Levallois technologies that form the EMP toolkit is investigated to reveal other dimensions of tool novelties. Through microscopic analyses, integrated with experimentation, the most outstanding aspect revealed in this study is the extensive evidence of hafting, which included the use of binding together with various techniques for tool design. A unique treatment was identified, never reported before, entailing the abrasion of cortical surfaces and protruding dorsal ridges. Other aspects include the clear preference for pointed tools as a leading morphological trend and the use of retouch as a mean to create durable working edges and facilitate grip arrangements. The analysis demonstrates the venue of use-wear to trace a wide variety of practices, including consumption-related (processing hunted game and edible plants) and craft-related (hide processing, woodworking, and perhaps stone working) activities that otherwise hardly leave a trace in the archaeological record. By exploring these features, the research provides important insights into early hominin behavior and way of life during the EMP, emphasizing the novelties brought by the earliest Homo sapiens out of Africa.